PENGARUH VOLATILITAS PENJUALAN, DAN TINGKAT HUTANG TERHADAP PERSISTENSI LABA DENGAN TAX AVOIDANCE SEBAGAI MODERASI - M. KHAIRUL SANI; LUH NADI (Jurnal Akuntansi dan Perpajakan Jayakarta, 2023)
The purpose of this study was conducted to examine and analyze the influence of sales volatility and debt levels on earnings persistence. Moderating Variables are useful for knowing whether these variables can strengthen or weaken the independent variable on the dependent variable. The research population is 118 companies in the Primary Consumer Goods (Consumer Non-Cyclicals) sector which are listed on the Indonesia Stock Exchange in 2017 – 2021. The type of research used is quantitative using secondary data. The method of determining the sample using purposive sampling. The number of samples is 56 companies. The research results show that sales volatility and debt levels moderated by tax avoidance simultaneously affect earnings persistence. Sales volatility affects earnings persistence. The level of debt has no effect on earnings persistence. Partially, the tax avoidance moderating variable has no effect on earnings persistence. In this study, tax avoidance was not able to moderate the relationship between sales volatility and earnings persistence, as well as the debt level variable, which was moderated by tax avoidance, proving that tax avoidance was not able to moderate the relationship between debt levels and earnings persistence.